T-cell control of Epstein-Barr virus-infected B cells is lost during P. falciparum malaria. - Whittle, H; Brown, J; Marsh, K; Greenwood, B; Seidelin, P; Tighe, H; Wedderburn, L (1984)
Endemic Burkitt's lymphoma, a tumour of children in which B lymphocytes are infected with Epstein-Barr virus (EBV), is common in areas of Africa where malaria is holoendemic. The tumour is characterized by chromosome translocations; usually the terminal portion of chromosome 8 containing the c-myc gene is translocated to chromosome 14, near the enhancer of the immunoglobulin heavy-chain locus. Less frequent are translocations of chromosome 8 to the kappa light-chain locus of chromosome 2 or to the lambda light-chain locus of chromosome 22. In vitro, EBV induces B cells to proliferate and secrete immunoglobulin and antibody. However, in vivo the infected B lymphocytes are under immunological control, so that abnormal proliferation is found only in immunosuppressed patients. Such patients are subsequently liable to develop lymphomas. Burkitt believed that the tumour he had described resulted from interaction between a virus(es) and a "reticuloendothelial system altered by chronic and heavy infection by malarial or other parasites". We report here that during an attack of Plasmodium falciparum malaria, T-cell subpopulations are radically altered so that, in vitro, B lymphocytes infected with EBV proliferate abnormally to secrete large amounts of immunoglobulin and antibody. This phenomenon offers some explanation for the increased incidence of Burkitt's tumour and the high levels of immunoglobulin found in people living in areas where P. falciparum malaria is common.